Analisis Kesulitan Penggunaan Partikel Wa, No, Ni, De pada Siswa MAN 1 Kebumen - Swari Araminta Safama; Lispridona Diner (DBSMB, Vocational College of Universitas Gadjah Mada, 2022)
Errors in using Japanese particles are often made by Japanese language learners in Indonesia. The purpose of this study is to identify 1) the types of difficulties in using particles in Japanese sentences, 2) the underlying causes faced by students in the language and culture class at MAN 1 Kebumen, and 3) their strategies for resolving these issues. Descriptive quantitative research methodologies were used in this study. Tests and questionnaires were employed as research tools, with questionnaires distributed to 61 students. The findings indicated that the majority of respondents had trouble using the wa, ni, and de particles. Specifically, 75% of students struggled to place the particles correctly in a sentence, and up to 61% of students had difficulties understanding how to use them. These problems were caused by both internal and external factors, including a lack of willingness to learn about particles, inadequate explanations of particle functions in the textbook, insufficient self-learning of particle meaning and usage after class, and a teaching style perceived as less diversified by the students. To overcome these challenges, students employed various strategies such as taking notes about particles, searching for particle functions on the internet, consulting others who were more knowledgeable about the subject, asking friends, and seeking direct assistance from the teacher.